Common Diseases of Silkworm and Their Management – A Comprehensive Overview - Kiruthika C; Susikaran S; Karthick Mani Bharathi B (International Journal of Insects, 2025)
Silkworms (Bombyxmori L.), pivotal to the sericulture industry, are susceptible to various diseases that significantly impact cocoon production and quality. Common silkworm diseases include viral, bacterial, fungal, and protozoan infections. Prominent viral diseases, such as nuclear polyhedrosis (NPV) and cytoplasmic polyhedrosis (CPV) often cause mass mortality in larvae. Bacterial diseases, like flacherie, are typically induced by poor hygiene and environmental stress. Fungal infections, including muscardine caused by Beauveria bassiana, proliferate in high humidity, thus leading to extensive larval mortality. Protozoan diseases, especially pebrine caused by Nosema bombycis, are highly contagious and can devastate silkworm populations. Effective management of silkworm diseases necessitates an integrated approach encompassing preventive, curative, and environmental strategies. Preventive measures include maintaining stringent hygiene in rearing houses, regular disinfection, and ensuring the use of disease-free silkworm eggs. Environmental management involves controlling temperature, humidity, and ventilation to create unfavourable conditions for pathogen proliferation. Infected larvae should be promptly identified and removed to prevent disease spread. Biocontrol agents and plant-based remedies are gaining prominence as eco-friendly alternatives to chemical treatments. Advanced diagnostic techniques, including PCR and ELISA, have improved early disease detection and monitoring. This abstract highlights the etiology, symptoms, and management strategies for the common diseases of silkworms, thus emphasizing sustainable sericulture practices. Strengthening research in disease-resistant silkworm breeds and biotechnological interventions offers a promising avenue for minimizing losses and enhancing sericulture productivity.
Keywords: Coccidiosis; Nuclear Polyhedrosis Virus; Silkworms; Silkworms diseases; sericulture